UTILIZAÇÃO DE TECNOLOGIAS MÓVEIS NO CONTROLE DA QUALIDADE NO CANTEIRO DE OBRAS - Rey, Rafaela; Costa, Dayana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the last years, Brazil has been facing an economic slowdown. This scenario of uncertainties shows the need of the construction industry to reinvent itself, investing in planning, enhancing productivity, efficiency and quality to meet an increasingly demanding market. Although quality management in construction is such an important issue, there are few studies about the control systems that produce information in a systematic and agile way. It is necessary which these systems are capable of overcoming the inherent characteristics of the construction, and assist the quality improvement of the works. Therefore, there is a need to develop methods and processes that seek to improve the quality management and information. Thus, with the aim of improving the processes, we sought to evaluate the use of mobile technology at the building site through two case studies using different software. Questionnaires were applied, and interviews were conducted to obtain users' perceptions about the applicability and contributions of technology in improving the quality of the construction work. Some criteria were identified for the evaluation of the adoption of the technology and it was possible to confirm its great potential of use.